2020
DOI: 10.3390/brainsci10120933
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology, Biomarkers, and Therapeutic Modalities Associated with Skeletal Muscle Loss Following Spinal Cord Injury

Abstract: A spinal cord injury (SCI) may lead to loss of strength, sensation, locomotion and other body functions distal to the lesion site. Individuals with SCI also develop secondary conditions due to the lack of skeletal muscle activity. As SCI case numbers increase, recent studies have attempted to determine the best options to salvage affected musculature before it is lost. These approaches include pharmacotherapeutic options, immunosuppressants, physical activity or a combination thereof. Associated biomarkers are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 74 publications
(177 reference statements)
0
8
0
Order By: Relevance
“…The cross-sectional area of the skeletal muscle (which represents approximately 40% of the body weight) decreases fast in the following 1-17 months after a trauma. Muscular atrophy in patients with SCI is partially explained by the rapid changes in the quality of muscle proteins, activating proteolytic enzymes and proteases from mitochondria, the increase in the production of reactive oxygen species and the decrease in oxidative capacity [31,32]. Based on a previous study, Ishimoto et al used only ASM as the criterion for identifying patients with sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…The cross-sectional area of the skeletal muscle (which represents approximately 40% of the body weight) decreases fast in the following 1-17 months after a trauma. Muscular atrophy in patients with SCI is partially explained by the rapid changes in the quality of muscle proteins, activating proteolytic enzymes and proteases from mitochondria, the increase in the production of reactive oxygen species and the decrease in oxidative capacity [31,32]. Based on a previous study, Ishimoto et al used only ASM as the criterion for identifying patients with sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic inflammatory response and oxidative stress in skeletal muscle after SCI may be the mechanisms leading to atrophy (9,(67)(68)(69). At present, the known factors and related proteins involved in skeletal muscle atrophy include: tumor necrosis factor-alpha (TNF-α) and its receptor (70)(71)(72), human tumor necrosis factor-related weak apoptosis-inducing factor (TWEAK) and its receptor (56, 67, 73), interleukin-1β (IL-1β) (72,74), interleukin-6 (IL-6) and its receptor (75,76), growth factor (IGF-1) (77, 78), human dystrophin (Fbox-1, also known as Atrogin-1) (79, 80), musclespecific RING finger protein 1 (MuRF1) (79,80), peroxisome proliferator-activated receptor-γ coactivator-1α (PGC-1α) (20,58,81), fibroblast growth factor-inducible receptor 14 (Fn14) (73), reactive oxygen species (ROS) (20,68,82) and others. The discovery of these skeletal dystrophins has provided a deeper understanding of skeletal muscle atrophy at the molecular level and suggest the possibility of intervening via corresponding signaling pathways and factors to delay the atrophy process or promote skeletal muscle regeneration.…”
Section: Cytokines Associated With Skeletal Muscle Atrophy After Scimentioning
confidence: 99%
“…Skeletal muscle is an integral producer of IL-1 and IL-6 (97), healthy individuals can promote IL-6 levels through exercise, but under short-term exercise SCI patients lack such a regulatory mechanism due to skeletal muscle atrophy (101), and studies have found that endurance exercise can regulate the expression of IL-1 and IL-6 in skeletal muscle (103, 108), which may explain the positive effect of endurance training on skeletal muscle function and muscle strength after SCI (75,109).…”
Section: Interleukin /mentioning
confidence: 99%
“…Spinal cord injury (SCI) is often a devastating traumatic event, that leads to serious secondary health complications, including increased risks of diabetes and cardiovascular diseases [1,2]. Following SCI, significant muscle atrophy typically develops below the lesion site, primarily due to prolonged diminished contractile activity [3]. This muscle atrophy is typically marked by a decrease in muscle mass and cross-sectional area, particularly affecting muscles innervated by the spinal cord segments below the injury level, resulting in pronounced weakness and diminished function [4].…”
Section: Introductionmentioning
confidence: 99%